Starch/tea polyphenols nanofibrous films for food packaging application: From facile construction to enhance mechanical, antioxidant and hydrophobic properties. (30th October 2021) - Zhang, Die; Chen, Lei; Cai, Jie; Dong, Qi; Din, Zia-ud; Hu, Zhong-Ze; Wang, Guo-Zhen; Ding, Wen-Ping; He, Jing-Ren; Cheng, Shui-Yuan
Graphical abstract: Starch nanofibrous film with multifunctionality for promising food packaging Highlights: Flexibly starch nanofibrous films were prepared directly from pure starch. The fiber inter-connection improves hydrophobicity through the fibrous structure. TP incorporated starch fibrous films show high mechanical and antioxidant properties. Abstract: Starch based food packaging has been receiving increasing attention. However, the inherent poor properties of starch restrict its practical applications in the versatile material science field. In this study, a fast, simple, and environmentally friendly route to construct polyfunctional starch/tea polyphenols nanofibrous films (STNFs) by one-step temperature-assisted electrospinning was developed. The effects of introduction of tea polyphenols (TP) on the mechanical and antioxidant activity of STNFs were comprehensively investigated. Results of ABTS·+ free radical scavenging assay showed that the antioxidant activity of STNFs was endowed by addition of TP with optimum mechanical properties confirmed by tensile test. More interestingly, the hydrophobicity of STNFs was improved dramatically with increasing cross-linking time as indicated by water contact angle (WCA) measurement showing no effect on the antioxidant activity of the films. The results of this work offer a major step forward to promote functional starch-based materials for sustainable application in food packaging.